The Influence Of Sales Growth And Profitability On Capital Structure In Pharmaceutical Companies On The Indonesia Stock Exchange - Singgih Abdul Pazri; John Sihar Manurung; Lily Maryam Nasution (CERED Indonesia Institute, 2023)
This research aims to determine the influence of sales growth and profitability on the capital structure of pharmaceutical companies on the Indonesia Stock Exchange during the period 2018-2021. The research population includes 11 pharmaceutical companies listed on the Indonesia Stock Exchange from 1981 to 2020. In this study, purposive sampling technique was used to select 9 companies as samples based on specific considerations. This research is explanatory in nature with a quantitative approach. Data analysis was carried out using multiple linear regression method with the assistance of Eviews 12 software. The t-test results show that, partially, only sales growth has a positive and significant impact on the capital structure, while profitability does not have a significant influence. However, the F-test results show that, simultaneously, sales growth and profitability have a significant influence on the capital structure of pharmaceutical companies. The research results indicate that 55.4% of the variation in the capital structure can be explained by sales growth and profitability, while the remaining 44.6% is influenced by other unexamined factors in this research model. In conclusion, sales growth plays an important role in shaping the capital structure of pharmaceutical companies, while profitability is not a significant determining factor.